POSISI HUKUM KORBAN PERZINAHAN YANG DILAPORKAN ATAS TINDAK PIDANA KESUSILAAN BERDASAR UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Hartanto Hartanto (Fakultas Hukum Universitas Kristen Indonesia, 2020)
The use of information and communication technology on the one hand contributes to the improvement of human welfare, but on the other hand, advances in information and communication technology can be used to commit acts that are against the law. Adultery is a social reality that often occurs, this discussion is related to the legal position of victims of adultery who are reported as crimes of decency based on law number 19 of 2016 concerning information and electronic transactions. The discussion uses doctrinal legal research methods and is limited to adding interviews as material to write down the object of the case that occurs. In the discussion section, it will examine the extent of criminal responsibility that can be borne by the perpetrator, while on the other side he is the victim. Keywords : information technology, legal position, criminal responsibility, victims